2014
DOI: 10.1104/pp.114.242628
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Dysfunction Causes Multiple Defects in Cell Cycle Progression in the Arabidopsis crumpled leaf Mutant    

Abstract: The majority of research on cell cycle regulation is focused on the nuclear events that govern the replication and segregation of the genome between the two daughter cells. However, eukaryotic cells contain several compartmentalized organelles with specialized functions, and coordination among these organelles is required for proper cell cycle progression, as evidenced by the isolation of several mutants in which both organelle function and overall plant development were affected. To investigate how chloroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…Here, we found that sog1 is hypersensitive to genotoxins targeting organelle DNA, suggesting that retrograde signalling pathways are activated by chloroplast DNA damage to trigger SOG1 activity. Indeed, it has been shown previously that ROS production in organelles activates ATM and the DDR pathway (Yi et al, 2014), and that chloroplast dysfunction induces the expression of SOG1 target genes (Hudik et al, 2014), some of which could be involved in the protection or repair of organelle genomes. A plethora of retrograde signalling routes have been described (de Souza et al, 2017), however, and further studies will be needed to determine how they are connected to the DDR.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that sog1 is hypersensitive to genotoxins targeting organelle DNA, suggesting that retrograde signalling pathways are activated by chloroplast DNA damage to trigger SOG1 activity. Indeed, it has been shown previously that ROS production in organelles activates ATM and the DDR pathway (Yi et al, 2014), and that chloroplast dysfunction induces the expression of SOG1 target genes (Hudik et al, 2014), some of which could be involved in the protection or repair of organelle genomes. A plethora of retrograde signalling routes have been described (de Souza et al, 2017), however, and further studies will be needed to determine how they are connected to the DDR.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular growth and chloroplast replication are tightly regulated cellular processes (Wittenberg & Reed, 2005; Hudik et al ., 2014) and are shown to be coordinated in diatoms (Gillard et al ., 2008). A strong transcript level response at 4 h of silicon starvation was documented in T. pseudonana and occurred while nearly half of the population continued to progress through the cell cycle (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the cell-cycle phase affected by MOS1, we analyzed the expression of five cell-cycle genes that have expression in specific cell-cycle phases in mos1. CDT1 and MCM2 are both associated with the G1/S transition and early S-phase; CYCD3;1 is predominantly at the G1/S transition; PCNA1 is expressed throughout S-phase; and CDC20.1 is expressed at the G2/M transition (Menges et al, 2002;Kevei et al, 2011;Hudik et al, 2014). We chose the fifth true leaf from plants whose eighth and ninth true leaves just became visible, so that the selected leaves were at a comparable developmental stage.…”
Section: Cycd3;1 May Mediate the Endoreduplication Effect Of Mos1mentioning
confidence: 99%